1982
DOI: 10.1007/bf00039206
|View full text |Cite
|
Sign up to set email alerts
|

Use of the SDS-sedimentation test and SDS-polyacrylamidegel electrophoresis for screening breeder's samples of wheat for bread-making quality

Abstract: INDEX WORDSTriticum aestivum, wheat, glutenin, SDS-sedimentation test, SDS-polyacrylamidegel-electrophoresis, baking quality selection. SUMMARY Gelprotein or SDS-insoluble gel-forming glutenin was isolated from wheat flour by extraction with an aqueous 1.5% SDS solution. Remarkable intervarietal differences were observed both in amount and subunit composition of these proteins.The amount of gelprotein and the SDS-sedimentation volume both proved to be good parameters for the bread-making quality of wheat culti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
78
5
4

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(97 citation statements)
references
References 10 publications
10
78
5
4
Order By: Relevance
“…In our results using 144 DH lines with a wide range of flour protein contents, it was revealed that the genotypic group of Glu-D1d had better SLV than that of Glu-D1a. This result is in agreement with findings in previous studies , Lagudah et al 1987, Lawrence et al 1984, Moonen et al 1982. In addition, the genotypic group of Glu-B3b had better SLV than that of Glu-B3g.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In our results using 144 DH lines with a wide range of flour protein contents, it was revealed that the genotypic group of Glu-D1d had better SLV than that of Glu-D1a. This result is in agreement with findings in previous studies , Lagudah et al 1987, Lawrence et al 1984, Moonen et al 1982. In addition, the genotypic group of Glu-B3b had better SLV than that of Glu-B3g.…”
Section: Discussionsupporting
confidence: 93%
“…According to many previous reports, Glu-D1d has a positive effect on loaf volume , Lagudah et al 1987, Lawrence et al 1984, Moonen et al 1982. In our results using 144 DH lines with a wide range of flour protein contents, it was revealed that the genotypic group of Glu-D1d had better SLV than that of Glu-D1a.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…There has been evidence to suggest that the SDS sedimentation test can be independently used to predict the bread baking potential and strength of wheat varieties (Moonen et al 1982;Greenaway et al 1966). On the basis of SDS sedimentation test, HI 977 could be classified as a good bread quality variety, while C 306 as being poor bread wheat quality.…”
Section: Flour Characteristics Analysismentioning
confidence: 99%
“…Alleles at three Glu-1 loci represent different effects on bread-making quality. HMWG subunits 5+10 coded by Glu-D1 show a much larger effect on the physical properties of dough than subunits 2+12 (Payne et al, 1981, Moonen et al, 1982. Most Japanese wheat cultivars, which show a poor bread-making quality, shared subunits 2+12, 2.2+12, and 4+12 at Glu-D1 (Nakamura et al, 1999).…”
mentioning
confidence: 99%